Pengaruh Implementasi Corporate Governance Terhadap Pengungkapan Sukarela (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2021) - Nauval Rifky Mipisca; Ratna Septiyanti (Journal on Education, 2024)
The purpose of this study is to identify and analyze how much influence the implementation of Corporate Governance has on voluntary disclosure of manufacturing companies listed on the Indonesian Stock Exchange for the 2017-2021 period. There are four principles that must be applied so that the objectives of good corporate governance can be achieved, namely fairness, accountability, transparency and responsibility. Therefore, it is mandatory for all organs in the company to implement these principles, so in this research the author uses the variables independent board of commissioners, managerial ownership, and institutional ownership for voluntary disclosure. The population in this research is all manufacturing sector companies listed on the Indonesia Stock Exchange during the observation period, namely 2017-2021. The sample determination in this research was carried out using non-probability purposive judgment sampling, where the sample was determined based on certain criteria determined by the author and has limitations in terms of generalization. The results indicate that partially, the variables of independent board of commissioners and managerial ownership do not affect voluntary disclosure in the company's annual reports. However, institutional ownership variable significantly influences voluntary disclosure in the company's annual reports.